Sense of coherence, occupational stressors, and mental health among Japanese high school teachers in Nagasaki prefecture: a multiple regression analysis - Miho Kuwato; Yuko Hirano (BMC, 2020)
Abstract Background International research has indicated that teachers have an increased risk of mental disorders and work-related stress, compared with those working in other fields. In Japan, the deterioration of teachers' mental health has recently become a serious social issue. Teaching is a high-stress occupation, and job stress can affect teachers' physical and mental health. This study aimed to determine how sense of coherence, job satisfaction, and workplace social support contribute to the mental health status of public and private high school teachers in Nagasaki Prefecture, Japan. Methods The analytic sample comprised 370 high school teachers from eight public and three private schools in Nagasaki Prefecture who answered an anonymous survey comprising the General Health Questionnaire (GHQ-12), which is a measure of mental health status, and questions regarding sociodemographic characteristics, occupational stressors, workplace social support systems, job satisfaction, and sense of coherence. A multiple regression analysis was conducted to identify the predictors of mental health. Results The survey was sent to 681 people, of whom 370 responded and were included in the analysis (effective response rate: 54.3%). The analysis indicated that sense of coherence was the strongest predictor of mental health (β = −.391, p < .0001), followed by workload stressors (β = .260, p < .0001), low job control (β = .099, p = .021), and job satisfaction (β = −.088, p = .040). Conclusion The results suggest that a greater sense of coherence and job satisfaction are associated with greater mental health. Meanwhile, workload stressors and low job control undermined mental health status.